Aryl Germanes as Ligands for Transition Polymetallic Complexes: Synthesis, Structure, and Properties. Issue 22 (21st May 2019) - Zaitsev, Kirill V.; Lam, Kevin; Poleshchuk, Oleg Kh.; Bezzubov, Stanislav I.; Churakov, Andrei V.
Abstract : A series of new carbonyl dichromium complexes bearing aryl germanes as ligands were prepared using improved approaches. The thermal reaction of Cr(CO)6 (1 ) with Me3 GeGePh3 (3 ) led to the formation of Me3 GeGePh[(η 6 ‐C6 H5 )Cr(CO)3 ]2 (3a ). The lithiation of [(η 6 ‐C6 H6 )Cr(CO)3 ] (2 ) with n BuLi followed by the addition of Me2 GeCl2 (4 ) or ClGeMe2 GeMe2 Cl (5 ) gave Me2 Ge[(η 6 ‐C6 H5 )Cr(CO)3 ]2 (4a ) and [(OC)3 Cr(η 6 ‐C6 H5 )]GeMe2 GeMe2 [(η 6 ‐C6 H5 )Cr(CO)3 ] (5a ), respectively. The molecular structures of3a and4a, in their crystal forms, were studied by X‐ray diffraction analysis. The crystals of oligogermane3a have shown to undergo a fully reversible phase transition at 160 K without any sign of decomposition. The complexes synthesized were also studied by multinuclear NMR, IR and UV/Vis spectroscopy, DFT calculations and electrochemistry. The presence of a Cr(CO)3 group in a range of oligogermanes has shown to impact on the physical and chemical properties of the compounds. Abstract : Novel polychromium carbonyl complexes based on arylgermanes were obtained; their properties were studied (XRD, NMR, DFT, IR, UV/Vis, EC) in details. The relationships between structure and properties were established for various types of substitution (terminal, median, gem ‐terminal).